KILAS BALIK SEJARAH, PENDIDIKAN ISLAM DALAM LINGKARAN ISU INTOLERANSI - YULIARNI YULIARNI (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2022)
The spirit of tolerance in Indonesia has decreased, marked by certain events, one of which is a conflict with a religious background. Islamic education is considered to be a vehicle for responding to this problem. However, the implementation of Islamic Education has not gone well. The purpose of this article is to describe how historical re-memory about Islamic Education in Indonesia can provide input to the current implementation of Islamic Education, to address intolerance. This research is qualitative research through document study. The results of this study found that Islamic Education in the past had been prepared by taking into account the plural reality in Indonesia.